The effects of a ten-week step aerobic training program on the body composition of college-aged women - Huntley, Elizabeth (My University, 1992)
The purpose of this study was to examine the effects of a 10-week step aerobic training program on the body composition of college-aged women (mean age - 19.6 yrs). Forty-six apparently healthy females between the ages of 18 and 25 years participated in the study. Subjects in the experimental group exercised 3 times per week for 10 weeks. The average intensity maintained during exercise was 150 bpm which represented 76% of HRmax. Eighteen experimental group Ss and 23 control group Ss were hydrostatically weighed and had maximal buttocks, thigh, and calf girths measured prior to and at the end of the study. The variables analyzed included body weight, inasimal buttocks girth, alasimal thigh girth, maximal calf girth, residual volume, lean body mass, Eat weight, hotly density, and percent body fat. The results showed a significant (p < -05) decrease for the experimental group in maximal thigh girth (1.0 cm). No significant (p > .05) between-group differences were observed for body weight, maximal buttocks girth, mnximal calf girth, body density, LBM, fat weight, or percent body fat.
Keywords: Step aerobics - Physiological aspects; Body composition; Exercise for women - Physiological aspects